UTILIZATION OF LAND WITH AQUA-PONIC SYSTEMS, MUSTARD GREENS AND AFRICAN CATFISH - Aminin Aminin; Andi Rahmad Rahim; Ummul Firmani; Sa’idah Luthfiyah; Sutrisno Adi Prayitno; Nur Maulida Safitri; Gawest Bagus Permana; Muhammad Haqul Yaqin (OJS Universitas Muhammadiyah Gresik, 2020)
Food needs in urban areas are increasing along with increasing population growth. The problem of population growth in urban areas is always followed by the construction of housing facilities. The development of housing facilities has an impact on the availability of land and water resources for fish farming and agriculture. Aquaponics technology is a combination of aquaculture and hyroponics technology in one system to optimize the function of water and space as maintenance media. Aquaponic system is a system that offers solutions related to narrow land use and limited water resources for fish and plant cultivation activities. In this community service activity, the aquaponics system was introduced to the community in the Dahanrejo area, with several activities carried out including the creation of an aquaponics unit, counseling and training given to the community on this aquaponics technique and unit. In carrying out community service activities there are several stages that need to be carried out including: location surveying, designing and testing of acuponic technology, counseling and training, monitoring and surveying. From the activities carried out, 20 people received training on how to use the land for freshwater fish cultivation and crop cultivation using aquaponics technology. In addition, an aquaponic unit was handed over to the kelurahan as a model for the existing community.